Telaah Penerapan PSAK 45 Dan PSAK 109 Dalam Rekonstruksi Akuntansi Pelaporan Keuangan Masjid - Fuad Yanuar AR; Widad Sarah Hanifah (LPPM ISNJ Bengkalis, 2020)
This research discusses the use of PSAK 45 and PSAK 109 in mosque financial reporting. The discussion focused on the concept of comprehensive and ideal implementation of mosque financial reporting. The results of the literature review of PSAK 45 and PSAK 109 ideally mosque financial statements should use PSAK 45 because the assumptions and management of mosques are far more complex sources and their use is not only about zakat and its distribution. However, the side of the simplicity of reporting and not reducing PSAK 45 rules is important in the disclosure and financial reporting of mosques. The mosque is also a zakat distribution body for reporting using PSAK 109 in a separate section.